The Engaged Leadership Development Model of Private School Principals - Rojratanavanit, Nipachcha; Charoenkul, Nantarat (Scholar: Human Sciences, 2018)
The objectives of this research were: 1.) to study the framework of the engaged leadership and leadership development model, 2.) to study the current and the ideal characteristics in engaged leadership of private school principals, and 3.) to develop an engaged leadership development model of private school principals. The population was general education private school principals in Bangkok.  The engaged leadership is defined as the ability to make the people engage with their jobs and organizations in three distinct ways: cognitively, emotionally, and behaviorally. It consisted of 5 components: 1.) directional leadership, 2.) motivational leadership, 3.) organizational leadership, 4.) inclusive leadership, and 5.) character core. The level of engaged leadership of private school principals, for the current characteristic, was performed at a high level. For the ideal characteristics, the overall score was at the highest level. The engaged leadership development model of private school principals is “the four-tier social change model of engaged leadership development”. The model was created to examine the engaged leadership development at four different levels: individual, group, social in organization, and organization. Additionally, the model provided two development experiences: 1.) formal development: cover 10% of total time, consisted of an initial self-evaluation test, self-learning from video lecture, and self-study through an interactive case scenario 2.) informal development: cover 90% of total time, which consisted of fieldbased learning with feedforward coaching, and post self-evaluation.